Supplementary Factual Data An Encyclopaedia of Land Transportation Models in Jakarta Using Multimedia Technologies - Dharmayanti, Dharmayanti; Permana, Dimas Dwi (Journal of Multimedia Trend and Technology, 2024)
The development of multimedia technology in various learning applications shows an increasing trend. According to the source (Head of IT Division AR & Co Indonesia) "the future of Augmented Reality has many advantages compared to Virtual Reality because users can see and touch digital objects and can interact with digital elements. Using Augmented Reality technology means that it will give birth to a new type of interaction between humans and computers". Therefore, research was conducted to create an encyclopedia of Jakarta transportation using augmented reality technology. This encyclopedia book is in the form of a book containing seven models of Jakarta transportation with a marker in the form of a QR-code. Each marker on each page displays a three-dimensional model of transportation along with its animation. This encyclopedia book about Jakarta transportation was created using the ARToolkit library software. To create a three-dimensional organ using the Blender 2.64 application, while making the marker using Adobe Photoshop CS4. The output of this application is in the form of a three-dimensional vehicle model along with animation that will be seen and the webcam is highlighted on the marker.